Projeto de Fortalecimento das Instituicoes e Infraestrutura do Mercado de Carbono no Brasil : Strengthening of the Brazilian Carbon Market's Institutions and Infrastructure [Bilingual] - World Bank (Washington, DC, 2013)
The worldwide carbon market is a reality. It has contributed to the implementation of projects that aim to reduce Greenhouse Gas (GHG) emissions in many different sectors and it has turned GHGs, represented by carbon, into economic assets that are no longer mere environmental liabilities. In this context, Brazil currently ranks third in the world in terms of the number of projects on the Clean Development Mechanism (CDM). Brazil pioneered the development of the first large scale methodology and registration for the first project in the history of the CDM. Despite Brazil's significant qualitative and quantitative participation in such projects, there is still great potential for the development of other types of CDM project activities. Given the new methodologies for CDM projects approved over the last few years and the programmatic CDM, which intends to reduce bureaucracy and accelerate the registration process for closely related projects, there exists an even greater potential for CDM projects in several sectors in Brazil. The main objective of this study was to identify the existing technical potential for low carbon projects as described above as well as to stimulate the implementation of low carbon projects in Brazil, thus contributing towards reducing and avoiding Brazil's current and projected emissions and inserting Brazil into the new low carbon economy. Generally speaking, the study focused on sectors where there is still a potential for the application of conventional techniques or technologies to reduce or avoid GHG emissions.